If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -11z = 9z + 7 Reorder the terms: -5 + -11z = 7 + 9z Solving -5 + -11z = 7 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. -5 + -11z + -9z = 7 + 9z + -9z Combine like terms: -11z + -9z = -20z -5 + -20z = 7 + 9z + -9z Combine like terms: 9z + -9z = 0 -5 + -20z = 7 + 0 -5 + -20z = 7 Add '5' to each side of the equation. -5 + 5 + -20z = 7 + 5 Combine like terms: -5 + 5 = 0 0 + -20z = 7 + 5 -20z = 7 + 5 Combine like terms: 7 + 5 = 12 -20z = 12 Divide each side by '-20'. z = -0.6 Simplifying z = -0.6
| 61.1=4.8h+9.5 | | (5x^2)+x-6=0 | | -(3y+3)-(-2y-4)=-3 | | x^2=15x+250 | | -2x^2+6X-3=0 | | -3(X+6)+4=-23 | | 12(t-6)+3t=5(3t+3)-11 | | 2x^2-12x+30=0 | | 3t^2-24t+30=0 | | 5+2(v+2)=3(v+7) | | 3(x+5)=-9 | | 124-p=628 | | (Y-25)+x=180 | | X^2=11-x | | 12(3x-4)=3(12x+2) | | -4x^2-9x-6=0 | | -(6x-4)=-4(x+6) | | (4+2n^3)+(5n^3+2)=0 | | -(7y+3)-(-6y-4)=-3 | | 3+3m-1=9m+6-5m | | 3(5X+4)-10X+9=51 | | 17+3y=5 | | Y-25=180 | | -2(x-8)+9=25 | | Y-25+x+52+96=360 | | -5-3b=4(b+4) | | x+2x+4=10 | | X+52+96=180 | | 26-2a=-2(6a+3)+2 | | y=1.5x-0.4 | | 4(2x+1)-3x=34 | | 3s+8=-9s |